Wave-induced horizontal diffusivity from optically sensed dye tracer fields in impermeable beach laboratory experiments - Thomas Pendergast; Ryan P. Mulligan; Benjamin Davidson; Alexandra Schueller; Kelsey Fall; Dawson Ethier; Nimish Pujara; Jack A. Puleo; Jason Olsthoorn (Coastal Engineering, 2026)

Genetic adaptation despite high gene flow in a range‐expanding population - Andy Lee; Benjamin N. Daniels; William Hemstrom; Cataixa López; Yuki Kagaya; Daisuke Kihara; Jean M. Davidson; Robert J. Toonen; Crow White; Mark R. Christie (Molecular Ecology, 2025)
Signals of natural selection can be quickly eroded in high gene flow systems, curtailing efforts to understand how and when genetic adaptation occurs in the ocean. This long‐standing, unresolved topic in ecology and evolution has renewed importance because changing environmental conditions are driving range expansions that may necessitate rapid evolutionary responses. One example occurs in Kellet's whelk ( Kelletia kelletii ), a common subtidal gastropod with an ~40‐ to 60‐day pelagic larval duration that expanded their biogeographic range northwards in the 1970s by over 300 km. To test for genetic adaptation, we performed a series of experimental crosses with Kellet's whelk adults collected from their historical (HxH) and recently expanded range (ExE), and conducted RNA‐Seq on offspring that we reared in a common garden environment. We identified 2770 differentially expressed genes (DEGs) between 54 offspring samples with either only historical range (HxH offspring) or expanded range (ExE offspring) ancestry. Using SNPs called directly from the DEGs, we assigned samples of known origin back to their range of origin with unprecedented accuracy for a marine species (92.6% and 94.5% for HxH and ExE offspring, respectively). The SNP with the highest predictive importance occurred on triosephosphate isomerase ( TPI ), an essential metabolic enzyme involved in cold stress response. TPI was significantly upregulated and contained a non‐synonymous mutation in the expanded range. Our findings pave the way for accurately identifying patterns of dispersal, gene flow and population connectivity in the ocean by demonstrating that experimental transcriptomics can reveal mechanisms for how marine organisms respond to changing environmental conditions.

A decade of erosion monitoring of coastal chalk cliff faces at a seasonal frequency (2010−2021) using terrestrial lasergrammetry and photogrammetry (Varengeville-sur-Mer and Dieppe, Normandy, France): Technical evolution and main results - Pauline Letortu; Stéphane Costa; Robert Davidson; Olivier Maquaire; Bastien Peuziat; Guillaume Thirard; Laurence David; Pauline Clain; Benjamin Troadec (Geomorphology, 2025)

Surface soil-dust contamination of Phalaris arundinacea grown on former lead mine sites: Implications for biomass use, phytoremediation and phytomanagement - Benjamin Nunn; Richard Lord; James Minto; Christine M. Davidson; Neelam Manzoor (Science of The Total Environment, 2025)

Linking Neotropical riparian and stream food webs: nocturnal foraging behavior and facilitation among decapods in response to added palm fruit - Alan P. Covich; Davidson Gomes Nogueira; Fabio de Oliveira Roque; Francisco Valente-Neto; José Sabino; Francisco Severo-Neto; Benjamin Z. Taylor; Carol Yang; William E. Nassar; Vanessa Silva; Rudi R. Laps; Franco Leandro Souza (Hydrobiologia, 2024)

The importance of delayed neutron precursors in gamma dose calculations for activated primary heat exchanger components in the Molten Salt Breeder Reactor - Eva E. Davidson; Benjamin R. Betzler; Yan Cao; Tingzhou Fei (Annals of Nuclear Energy, 2024)

De novo genome and transcriptome assembly of Kelletia kelletii, a coastal gastropod and fisheries species exhibiting a northern range expansion - Benjamin N. Daniels; Cassidy L. Andrasz; Nicholas Zarate; Andy Lee; Cataixa López; Paul Anderson; Robert J. Toonen; Mark R. Christie; Crow White; Jean M. Davidson (Frontiers in Marine Science, 2023)
Understanding the genomic characteristics of non-model organisms can bridge research gaps between ecology and evolution. However, the lack of a reference genome and transcriptome for these species makes their study challenging. Here, we complete the first full genome and transcriptome sequence assembly of the non-model organism Kellet’s whelk, Kelletia kelletii , a marine gastropod exhibiting a poleward range expansion coincident with climate change. We used a combination of Oxford Nanopore Technologies, PacBio, and Illumina sequencing platforms and integrated a set of bioinformatic pipelines to create the most complete and contiguous genome documented among the Buccinoidea superfamily to date. Genome validation revealed relatively high completeness with low missing metazoan Benchmarking Universal Single-Copy Orthologs (BUSCO) and an average coverage of ∼70x for all contigs. Genome annotation identified a large number of protein-coding genes similar to some other closely related species, suggesting the presence of a complex genome structure. Transcriptome assembly and analysis of individuals during their period of peak embryonic development revealed highly expressed genes associated with specific Gene Ontology (GO) terms and metabolic pathways, most notably lipid, carbohydrate, glycan, and phospholipid metabolism. We also identified numerous heat shock proteins (HSPs) in the transcriptome and genome that may be related to coping with thermal stress during the sessile life history stage. A robust reference genome and transcriptome for the non-model organism K. kelletii provide resources to enhance our understanding of its ecology and evolution and potential mechanisms of range expansion for marine species facing environmental changes.

A circular economy approach to drinking water treatment residue management in a catchment impacted by historic metal mines - Benjamin Nunn; Richard Lord; Christine M. Davidson (Journal of Environmental Management, 2023)

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Biogeochemical recuperation of lowland tropical forest during succession - Benjamin W. Sullivan; Rachel L. DuBose; Megan K. Nasto; Silvia Alvarez‐Clare; Camie M. Dencker; Fiona M. Soper; Kevin T. Shoemaker; F. Yoko Ishida; Joana Zaragoza‐Castells; Eric A. Davidson; Cory C. Cleveland (Ecology, 2019)
High rates of land conversion and land use change have vastly increased the proportion of secondary forest in the lowland tropics relative to mature forest. As secondary forests recover following abandonment, nitrogen (N) and phosphorus (P) must be present in sufficient quantities to sustain high rates of net primary production and to replenish the nutrients lost during land use prior to secondary forest establishment. Biogeochemical theory and results from individual studies suggest that N can recuperate during secondary forest recovery, especially relative to P. Here, we synthesized 23 metrics of N and P in soil and plants from 45 secondary forest chronosequences located in the wet tropics to empirically explore (1) whether there is a consistent change in nutrients and nutrient cycling processes during secondary succession in the biome; (2) which metrics of N and P in soil and plants recuperate most consistently; (3) if the recuperation of nutrients during succession approaches similar nutrient concentrations and fluxes as those in mature forest in ~100 yr following the initiation of succession; and (4) whether site characteristics, including disturbance history, climate, and soil order are significantly related to nutrient recuperation. During secondary forest succession, nine metrics of N and/or P cycling changed consistently and substantially. In most sites, N concentrations and fluxes in both plants and soil increased during secondary succession, and total P concentrations increased in surface soil. Changes in nutrient concentrations and nutrient cycling processes during secondary succession were similar whether mature forest was included or excluded from the analysis, indicating that nutrient recuperation in secondary forest leads to biogeochemical conditions that are similar to those of mature forest. Further, of the N and P metrics that recuperated, only soil total P and foliar δ 15 N were strongly influenced by site characteristics like climate, soils, or disturbance history. Predictable nutrient recuperation across a diverse and productive ecosystem may support future forest growth and could provide a means to quantify successful restoration of ecosystem function in secondary tropical forest beyond biomass or species composition.

Connectivity between the central nucleus of the amygdala and the bed nucleus of the stria terminalis in the non-human primate: neuronal tract tracing and developmental neuroimaging studies - Jonathan A. Oler; Do P. M. Tromp; Andrew S. Fox; Rothem Kovner; Richard J. Davidson; Andrew L. Alexander; Daniel R. McFarlin; Rasmus M. Birn; Benjamin E. Berg; Danielle M. deCampo; Ned H. Kalin; Julie L. Fudge (Brain Structure and Function, 2017)

Habitat modification in tidepools by bioeroding sea urchins and implications for fine‐scale community structure - Timothy M. Davidson; Benjamin M. Grupe (Marine Ecology, 2015)
By creating novel habitats, habitat‐modifying species can alter patterns of diversity and abundance in marine communities. Many sea urchins are important habitat modifiers in tropical and temperate systems. By eroding rocky substrata, urchins can create a mosaic of urchin‐sized cavities or pits separated by exposed, often flat surfaces. These microhabitats appear to harbor distinct assemblages of species. We investigated how a temperate rocky intertidal community uses three small‐scale ( 2 ) microhabitats created by or adjacent to populations of the purple sea urchin ( S trongylocentrotus purpuratus ): pits occupied by urchins, unoccupied pits, and adjacent flat spaces. In tidepools, flat spaces harbored the highest percent cover of algae and sessile fauna, followed by empty pits and then occupied pits. The Shannon diversity and richness of these sessile taxa were significantly higher in flat spaces and empty pits than in occupied pits. The composition of these primary space holders in the microhabitats also varied. Unlike primary space holders, mobile fauna exhibited higher diversity and richness in empty pits than in flat spaces and occupied pits, although results were not significant. The protective empty pit microhabitat harbored the highest densities of most trophic functional groups. Herbivores, however, were densest in flat spaces, concordant with high algal coverage. These results suggest the habitats created by S . purpuratus in addition to its biological activities alter community structure at spatial scales finer than those typically considered for sea urchins.

Assessing changes in numbers and distribution of large whale entanglements in Newfoundland and Labrador, Canada 1 - Steven Benjamins; Wayne Ledwell; Julie Huntington; Anthony Raphael Davidson (Marine Mammal Science, 2012)
Entanglements of large whales in commercial fisheries in Newfoundland and Labrador, Canada, have been consistently recorded since 1979, as part of a program aimed at releasing captured animals and reducing costs to fishermen. This data set represented an opportunity to identify fisheries posing particular entanglement risks to local whale populations. Data were assessed over the periods 1979–1992 and 1993–2008, corresponding to distinct phases in fisheries distribution and intensity. Between 1979 and 2008, 1,209 large whale entanglements were recorded in Newfoundland and Labrador. These were mostly humpback whales ( Megaptera novaeangliae ; 80%) and minke whales ( Balaenoptera acutorostrata ; 15%). Dramatic declines in reported inshore whale entanglement rates were observed following the 1992 moratorium on Atlantic cod ( Gadus morhua ) fisheries. Recently, more entanglements have been reported further offshore, largely due to expansion of fisheries targeting snow crab ( Chionoecetes opilio ). For all whale species, entanglement rates and associated mortality rates varied considerably in different fishing gear. Fractions of humpback and minke whales found dead in different fishing gear differed substantially, with minke whales far more likely to be found dead than humpback whales.